Conserved enhancers control notochord expression of vertebrate Brachyury - Kemmler, Cassie L; Smolikova, Jana; Moran, Hannah R; Mannion, Brandon J; Knapp, Dunja; Lim, Fabian; Czarkwiani, Anna; Hermosilla Aguayo, Viviana; Rapp, Vincent; Fitch, Olivia E; Bötschi, Seraina; Selleri, Licia; et al. (Nature communications, 2023)
The cell type-specific expression of key transcription factors is central to development and disease. Brachyury/T/TBXT is a major transcription factor for gastrulation, tailbud patterning, and notochord formation; however, how its expression is controlled in the mammalian notochord has remained elusive. Here, we identify the complement of notochord-specific enhancers in the mammalian Brachyury/T/TBXT gene. Using transgenic assays in zebrafish, axolotl, and mouse, we discover three conserved Brachyury-controlling notochord enhancers, T3, C, and I, in human, mouse, and marsupial genomes. Acting as Brachyury-responsive, auto-regulatory shadow enhancers, in cis deletion of all three enhancers in mouse abolishes Brachyury/T/Tbxt expression selectively in the notochord, causing specific trunk and neural tube defects without gastrulation or tailbud defects. The three Brachyury-driving notochord enhancers are conserved beyond mammals in the brachyury/tbxtb loci of fishes, dating their origin to the last common ancestor of jawed vertebrates. Our data define the vertebrate enhancers for Brachyury/T/TBXTB notochord expression through an auto-regulatory mechanism that conveys robustness and adaptability as ancient basis for axis development.
Keywords: dánio pruhované; Animals; Mammals; Brachyury Protein; Gene Expression Regulation, Developmental; lidé; Mice; fetální proteiny; Notochord; myši; proteiny T-boxu; Zebrafish; chorda dorsalis; savci; protein brachyurie; T-Box Domain Proteins; Fetal Proteins; zvířata; vývojová regulace genové exprese; Humans